Marked subcutaneous mast cell and eosinophilic infiltration associated with the presence of multiple Dirofilaria repens microfilariae in 4 dogs. (18th October 2016) - Mazaki‐Tovi, Michal; Reich, Michal; Karnieli, Adva; Kuzi, Sharon; Aroch, Itamar
Abstract: Dirofilaria repens is a parasitic nematode in the subcutaneous tissue of carnivores, including dogs and cats, transmitted by mosquitoes. Human beings may be accidental hosts. Infection of a dog with D repens was first reported in Palestine in 1934, and 2 additional cases were reported in dogs in Israel to date. This report describes D repens infection in 4 dogs in Israel that presented with subcutaneous masses, which were cytologically characterized by marked mast cell and eosinophil infiltration. In 3 cases, multiple microfilariae were present in the lesions; rare microfilariae were present in the 4 th case. In all 4 dogs, PCR of fine‐needle aspirates from the lesions were positive for D repens . The mast cells observed in all lesions were uniform and highly granulated, and with the presence of the microfilariae, a mast cell tumor was considered less likely. This report suggests that D repens infection‐associated subcutaneous lesions, characterized cytologically by massive mast cell and eosinophil infiltration, should be considered a differential diagnosis for mast cell tumor, especially in geographic locations endemic for this nematode. Notably, all 4 dogs were infected with D repens despite a routine prophylactic doramectin therapy administered every 3 months, probably due to the relatively long time interval between treatments.